PENINGKATAN EFISIENSI ENERGI SEBAGAI UPAYA MENGATASI DAMPAK PENGGUNAAN ENERGI PADA LINGKUNGAN - Suarna, Endang (Jurnal Teknologi Lingkungan, 2009)
As the energy consumption continues to increase, pollutants and greenhousegases emissions from the energy utilization also increases. The increase ofthose emissions has impacts on environmental problems that harmful for theecosystem and the population. Program action needed to reduce the energyconsumption. Improving the efficiency of energy use is the most effective wayto address simultaneously several national issues. It is not only can reduce theenergy consumption, but also it can reduce the pollutant and greenhouse gasesemissions. The program also can strengthen the national energy security. Theenergy efficiency program has been implemented in some countries, but Japan isthe most advance country on energy efficiency